Challenges encountered in a South African school nutrition programme - Tafirenyika Mafugu (SAGE Publishing, 2021)
Background: School Nutritional Programmes (SNP) provide meals at school to reduce hunger, nutrient deficiencies and improve class alertness among children in poor communities. The purpose of the research was to determine the challenges encountered in implementing the SNP in KwaZulu-Natal Province, South Africa in 2017. Design and methods: A cross-sectional study underpinned by a concurrent triangulation research design where interviews were used to collect qualitative data from stakeholders, and a questionnaire collected quantitative data from students. The set of qualitative data was thematically analysed. Descriptive and inferential statistics were used to analyse the quantitative data. Analysis of variance (ANOVA) and Tukey HSD test were used to compare the mean scores for food quality on different days of the week. Results: Both the quality and quantity of food were affected by delays in payment of food suppliers, lack of training of stakeholders, and poor kitchen facilities. Health problems experienced by students after eating the food made them reluctant to consume meals on some days. The Tukey HSD test indicated that the mean score for the quality of food served on Wednesday (3.2±1.3) was significantly higher than the mean score for the quality of the meal served on Friday (2.5±1.3). Conclusions: Late payment of food-suppliers and inadequate training of food-handlers affected the quality and quantity of the meals. The researcher recommends that the programme administrators should improve the frequency of payment for food suppliers, training of food handlers, and find alternative meals for students who do not consume the regular meals due to various reasons.